THE INFLUENCE OF STIGMA, DISCRIMINATION, AND ANTIRETROVIRAL THERAPHY ADHERENCE ON THE QUALITY OF LIFE OF PEOPLE LIVING WITH HIV/AIDS IN GORONTALO CITY - Amelia, Sherin Dwi; Irwan, Irwan; Arsad, Nikmatisni (International Journal of Health Science & Medical Research, 2025)
HIV/AIDS is a chronic disease with a steadily increasing prevalence, requiring serious attention, particularly in efforts to improve the quality of life of those affected. Persistent stigma and discrimination present significant psychosocial challenges. Meanwhile, antiretroviral therapy, as the primary treatment for individuals with HIV/AIDS, plays a vital role in maintaining health stability. These three aspects are key determinants that can comprehensively influence the quality of life of people living with HIV/AIDS. This study aims to examine the influence of stigma, discrimination, and adherence to antiretroviral therapy on the quality of life of people living with HIV/AIDS in Gorontalo City. This study employed an analytical survey with a cross-sectional design. The sample consisted of 69 individuals living with HIV-AIDS, selected through purposive sampling. Data were analyzed using ordinal logistic regression with a significance level of 0,05. The analysis revealed that stigma (p-value = 0,000, OR 0,028) and discrimination (P-value = 0,006, OR = 7,32) had a significant influence on the quality of life of people living with HIV-AIDS in Gorontalo City However, adherence to antiretroviral therapy showed no significant impact (P-value = 0,708, OR = 0,761) on their quality of life. This study recommends efforts to raise public awareness about HIV/AIDS and to address the detrimental effects of stigma and discrimination on people living with the disease.